Optimal operation of a south double-skin facade - Gratia, Elisabeth; De Herde, André (Energy and buildings, 2004)
There is an increasing demand for higher quality office buildings. Occupants and developers of office buildings ask for a healthy and stimulating working environment. Double-skin facades are appropriate when buildings are subject to great external noise and wind loads. A further area of application is in rehabilitation work, when existing facades cannot be renewed, or where this is not desirable. Double-skin facades have a special esthetic of their own, and this can be exploited architecturally to great advantage. However there are still relatively few buildings in which double-skin facades have actually been realized, and there is still too little experience of their behaviour in operation. In this matter, we choose to study a multistory double-skin facades behaviour. Simulations were realized with TAS software on the building proposed in the frame of the subtask A of the Task 27 (performance of solar facade components) of the International Energy Agency. Simulations were performed on the chosen building with and without double-skin facades. We decide to study eight types of days; and we analyze the double-skin facade behaviour for various operations. The thermal behaviours of the building with and without double-skin are compared. The study of these eight cases showed the importance of the dynamic use of the double-skin. The operation of this one must be obligatorily related to the climatic conditions as well external as interior and a bad operation of the double-skin could lead to catastrophic results.